2009
DOI: 10.1016/j.expneurol.2008.10.025
|View full text |Cite
|
Sign up to set email alerts
|

L1 cell adhesion molecule is essential for the maintenance of hyperalgesia after spinal cord injury

Abstract: Spinal cord injury (SCI) results in a loss of normal motor and sensory function, leading to severe disability and reduced quality of life. A large proportion of individuals with SCI also suffer from neuropathic pain symptoms. The causes of abnormal pain sensations are not well understood, but can include aberrant sprouting and reorganization of injured or spared sensory afferent fibers. L1 is a cell adhesion molecule that contributes to axonal outgrowth, guidance and fasciculation in development as well as syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 89 publications
(142 reference statements)
2
37
0
Order By: Relevance
“…Given that several studies have shown a stimulatory effect of VEGF on axonal growth (Zachary, 2005), and that aberrant axonal growth/sprouting underlies the development of neuropathic pain post-SCI (Hoschouer et al, 2009;Kalous et al, 2007;Macias et al, 2006), we hypothesized that VEGF 165 stimulates excessive axonal growth, and thus increases mechanical hypersensitivity in SCI rats (Fig. 2).…”
Section: Vegf and Axonal Abundancementioning
confidence: 99%
See 3 more Smart Citations
“…Given that several studies have shown a stimulatory effect of VEGF on axonal growth (Zachary, 2005), and that aberrant axonal growth/sprouting underlies the development of neuropathic pain post-SCI (Hoschouer et al, 2009;Kalous et al, 2007;Macias et al, 2006), we hypothesized that VEGF 165 stimulates excessive axonal growth, and thus increases mechanical hypersensitivity in SCI rats (Fig. 2).…”
Section: Vegf and Axonal Abundancementioning
confidence: 99%
“…2). In previous studies (Hoschouer et al, 2009;Kalous et al, 2007;Macias et al, 2006), researchers also reported that SCI pain was associated with excessive sprouting of pain-processing unmyelinated axons expressing calcitonin gene-related peptide (CGRP). Therefore we analyzed the effect of VEGF 165 on CGRP labeling in the dorsal horns in two regions: (1) laminae I and II (which normally contain most of the CGRP-positive axons), and (2) laminae III-V (which normally contain only a small number of CGRP-expressing axons).…”
Section: Vegf and Axonal Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…and antibiotics (5 mg=kg gentocin, s.q.) for 5 days following surgery, and bladder expression twice a day for the duration of the study (Hoschouer et al, 2008).…”
Section: Animals and Surgerymentioning
confidence: 99%